Impact of COVID‐19 on social prescribing across an Integrated Care System: A Researcher in Residence study. (30th March 2022) - Westlake, Debra; Elston, Julian; Gude, Alex; Gradinger, Felix; Husk, Kerryn; Asthana, Sheena
Abstract: Emerging evidence suggests that connecting people to non‐medical activities in the community (social prescribing) may relieve pressure on services by promoting autonomy and resilience, thereby improving well‐being and self‐management of health. This way of working has a long history in the voluntary and community sector but has only recently been widely funded by the National Health Service (NHS) in England and implemented in Primary Care Networks (PCNs). The COVID‐19 global pandemic coincided with this new service. There is wide variation in how social prescribing is implemented and scant evidence comparing different delivery models. As embedded researchers within an Integrated Care System in the Southwest of England, we examined the impact of COVID on the implementation of social prescribing in different employing organisations during the period March 2020 to April 2021. Data were collected from observations and field notes recorded during virtual interactions with over 80 social prescribing practitioners and an online survey of 52 social prescribing practitioners and middle managers. We conceptualise social prescribing as a pathway comprising access, engagement and activities, facilitated by workforce and community assets and strategic partnerships. We found that these elements were all impacted by the pandemic, but to different degrees according to the way the service was contracted, whether referrals (access) and approach (engagement) were universal ('open') or targeted ('boundaried') and the extent to which practitioners' roles were protected or shifted towards immediate COVID‐specific work. Social prescribers contracted in PCNs were more likely to operate an 'open' model, although boundaries were developing over time. We suggest the presence of an explicit, agreed delivery model (whether 'open' or 'boundaried') might create a more coherent approach less likely to result in practitioner role drift, whilst allowing flexibility to adjust to the pandemic and enhancing practitioner satisfaction and well‐being. The potential consequences of different models are examined.